Optimalisasi Fungsi Paru Melalui Edukasi dan Pemeriksaan Spirometri Pada Masyarakat Usia Produktif - Triyana Sari; Alexander Halim Santoso; Farell Christian Gunaidi; Muhammad Rifat Umar Alwini; Kenzie Rafif Ramadhani (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Lung health plays a crucial role in maintaining metabolic functions and individual productivity, particularly during adulthood. Undetected pulmonary dysfunction may significantly reduce work capacity and overall quality of life. This community service initiative aimed to conduct early screening of lung function using spirometry among the adult population at Asisi Church, South Jakarta. The program was implemented through the Plan-Do-Check-Act (PDCA) cycle, involving health education, spirometry assessment, result evaluation, and the provision of medical follow-up advice. A total of 62 participants took part in the activity. The spirometric examination revealed average values of vital capacity (VC) at 69.53%, FVC at 61.58%, FEV1 at 68.69%, and FEV1% at 114.13%. All participants were classified as “normal/at risk,” indicating a need for continued monitoring despite the absence of clinical symptoms. This program highlights the importance of early detection of pulmonary dysfunction and the critical role of health education in preventing chronic respiratory diseases such as COPD. Through collaborative efforts between academic institutions and the local community, this initiative demonstrates the effectiveness of community-based preventive strategies in raising awareness of lung health and encouraging healthy lifestyle practices for sustainable quality of life. Keywords: Lung Function, Vital Capacity, Screening